A Didactic Approach to the Development of AI Competencies - Karimova , Diyora (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
In this thesis, the content of the development of students’ competencies in the use of artificial intelligence in the process of higher education is substantiated from a didactic point of view. The goal is to determine the composition of competence, to harmonize it with the content of the subject and the system of tasks. The methodology is based on analytical-synthetic, modeling, and pedagogical design approaches. Scientific novelty is expressed in the design of competencies through a three-layer content model.